Modern approaches and educational technologies for forming a culture of safe activities of students in universities: a theoretical aspect - Osipov, A.Yu.; Ponomarev, V.V.; Poboronchuk, T.N.; Prihodov, D.S. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to conduct a theoretical analysis and systematise modern approaches and educational technologies for forming a culture of safe living among students at universities, identify current trends and problems in this educational and applied process, and develop an organisational and pedagogical algorithm for its improvement. Methods and structure of the study. During 2025, an analysis of scientific and methodological literature and educational programmes for students in the educational and applied discipline of ‘Life Safety’ was conducted. In the course of the analytical work, a large array of sources on the topic of the work was analysed, as well as a number of educational and methodological literature on the discipline ‘Life Safety’. The collected factual material was systematised, and the main directions and trends in the formation of a culture of safe life activities among students in higher education institutions were identified. All this contributed to the identification of basic problems, as well as the development of comprehensive educational and applied directions for adjusting the content of the educational process of preparing students in higher education institutions in the country for safe life activities. Results and conclusions. The analytical work carried out, aimed at analysing, systematising and identifying the effectiveness of the modern process of forming a culture of safe living among students in the country’s universities, showed the need to develop the following scientific and methodological provisions to improve the current educational practice in Life Safety: - the need to develop a common strategy for forming a culture of safe living among the country’s population, starting from preschool age and continuing through to retirement age; - to develop a single textbook and educational programme on the subject of ‘Life Safety’ for all educational institutions and age groups of the population; - improving the training of teachers in life safety at the country’s teacher training universities, taking into account new natural, social, environmental and other challenges facing humanity; - developing standards for the preparedness and control of the population for safe living (similar to the GTO); - include in the scientific speciality: 5.8.4 - Physical Culture and Professional Physical Training, scientific direction: ‘Human Life Safety’, thereby expanding this direction, which will activate and expand scientific and methodological developments in the practical discipline of life safety; - expand and improve the material and technical base for the correct formation of practical skills and abilities of university students for safe life activities.